Combined Microbial Consortium Inoculation and Black Locust Planting Is Effective in the Bioremediation of Waste Drill Cuttings - Liu, Hanjun; Chen, Lirong; Wang, En T.; Liu, Yihao; Zhang, Lingzi; Zhao, Ke; Gu, Yunfu; Yu, Xiumei; Ma, Menggen; Penttinen, Petri; Zhang, Xiaoping; Huang, Min; et al. (Frontiers in Microbiology, 2020)
Waste drill cuttings (WDC), produced during gas and oil drilling consists of 80% of rock cuttings and 20% of drilling muds, are an increasingly potent source of environmental pollution. We studied the efficiency of bioaugmentation and phytoremediation to remediate WDC in an experiment where WDC was incubated in a greenhouse for 120 days with and without black locust (Robinia pseudoacacia) plant and with or without bacterial and fungal consortium inoculant. The pollutant removal rates were highest in inoculated and planted treatment, followed by inoculated treatment and planted treatment. The small decrease in contaminant level in the control treatment suggested that indigenous microorganisms in WDC had little pollutant degradation capability. In the inoculated and planted treatments, after 120 days the germination rate of red clover seeds was on the same level as in the natural soil, showing a marked decrease in the ecotoxicity of WDC. Both the bacterial and fungal richness and bacterial diversity increased in all the treatments over time, whereas the fungal diversity increased only in the not inoculated treatments. The activity of laccase enzyme played a key role in the bioremediation process. The enzyme activities were mostly governed by inoculated consortium and soil bacterial community, and black locust affected the bioremediation mainly through its effect on N content that further affected bacterial and fungal communities.